A Novel Synthesis of Malic Acid Capped Silver Nanoparticles using Solanum lycopersicums Fruit Extract - Umadevi, M.; Bindhu, M.R.; Sathe, V. (Journal of materials science & technology, 2013)
Integration of green chemistry principles to nanotechnology is one of the key issues in nanoscience research. The development of the concept of green nanoparticle preparation has been growingly needed for environmentally benign metal nanoparticle synthesis protocols to avoid adverse effects in medical applications. Keep this in mind, in the present study, silver nanoparticles were synthesized using Solanum lycopersicums fruit extract. The prepared silver nanoparticles were characterized by UV-visible spectroscopy, Fourier transform infrared spectroscopy, Raman spectroscopy, scanning electron microscopy and transmission electron microscopy techniques. The surface plasmon resonance peak was found at 445 nm. The synthesized silver nanoparticles were spherical in shape with the average size of 10 nm. The citric acid present in S. lycopersicums fruit extract acted as reducing agent and malic acid was responsible for capping of the bioreduced silver nanoparticles.